Mercury distribution in different environmental matrices in aquatic systems of abandoned gold mines, Western Colombia: Focus on human health (2021)
Total mercury (THg), methylmercury (MeHg) in water, sediments, macrophytes, fish and human health risks were analyzed and assessed from abandoned gold mining ponds (AGMPs)/ mining areas in Western Colombia to know its present environmental condition. Concentrations of THg in water (avg. 13.0 ± 13.73 ng L-1) was above the EPA threshold level (12 ng L-1), suggesting possible chronic effects. Sediment sample revealed that the ponds are methylated (%MeHg: 3.3–11). Macrophyte Eleocharis elegans presented higher THg content in the underground biomass (0.16 ± 0.13 µg g-1 dw) than in the aerial biomass (0.05 ± 0.04 µg g-1 dw) indicating accumulation of THg. MeHg was the most abundant chemical species in fish (MeHg/THg: 83.2–95.0%), signifying higher bioavailability and its risk towards human health. Fish samples (15%) indicate that THg were above WHO limit (0.5 µg g), particularly in Ctenolucius beani, Hoplias malabaricus and lowest in Sternopygus aequilabiatus and Geophagus pellegrini. Bioaccumulation and biomagnification of MeHg were higher in the carnivores representing a source of exposure and potential threat to human health. Fulton's condition factor (K) for bioaccumulation indicate a decrease with increasing trophic level of fishes. Overall results suggest, mercury species found in different AGMPs compartments should be monitored in this region. © 2020 Elsevier B.V.